2023
DOI: 10.3390/ijms24065222
|View full text |Cite
|
Sign up to set email alerts
|

Limonene, a Monoterpene, Mitigates Rotenone-Induced Dopaminergic Neurodegeneration by Modulating Neuroinflammation, Hippo Signaling and Apoptosis in Rats

Abstract: Rotenone (ROT) is a naturally derived pesticide and a well-known environmental neurotoxin associated with induction of Parkinson’s disease (PD). Limonene (LMN), a naturally occurring monoterpene, is found ubiquitously in citrus fruits and peels. There is enormous interest in finding novel therapeutic agents that can cure or halt the progressive degeneration in PD; therefore, the main aim of this study is to investigate the potential neuroprotective effects of LMN employing a rodent model of PD measuring parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Noticeably, there was a considered decrease in the level of lipid and protein oxidation which was regulated by bornyl acetate and menthol treatment. On the other hand, natural sources of antioxidants are used to enhance the normal mechanism, hence the bio-active agents with one such effective derivative monoterpene has been reported to scavenge the free radical thus reducing the oxidation of other cellular molecules [113,114]. Citronellol enhanced anti-oxidant enzymes against rotenone induced neuronal damage reduced the level of lipid peroxidation [115], reduction in advanced glycation end products were reported by 1,8-cineole [116] and dihydroactinidiolide signi cantly reduced lipid peroxidation and protein carbonylation in SH-SY5Y cells induced by sodium dithionite, glutamate, amyloid β and colchicine [117].…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, there was a considered decrease in the level of lipid and protein oxidation which was regulated by bornyl acetate and menthol treatment. On the other hand, natural sources of antioxidants are used to enhance the normal mechanism, hence the bio-active agents with one such effective derivative monoterpene has been reported to scavenge the free radical thus reducing the oxidation of other cellular molecules [113,114]. Citronellol enhanced anti-oxidant enzymes against rotenone induced neuronal damage reduced the level of lipid peroxidation [115], reduction in advanced glycation end products were reported by 1,8-cineole [116] and dihydroactinidiolide signi cantly reduced lipid peroxidation and protein carbonylation in SH-SY5Y cells induced by sodium dithionite, glutamate, amyloid β and colchicine [117].…”
Section: Discussionmentioning
confidence: 99%
“…Derivatives of diol 1, compounds 3 and 4, showed neuroprotective effects in vitro and in several experimental mice models (MPTP-, rotenone-, and haloperidol-induced) of Parkinson's disease [66,67] (Figure 2). Neuroprotective potential was demonstrated also for carvacrol [68][69][70], limonene [71][72][73], geraniol [74,75], citronellol [76], carveol [77], 1,8-cineole [78], paeoniflorin [79], α-pinene [80], and linalool [81].…”
Section: Introductionmentioning
confidence: 90%
“…Derivatives of diol 1, compounds 3 and 4, showed neuroprotective effects in vitro and in several experimental mice models (MPTP-, rotenone-, and haloperidol-induced) of Parkinson's disease [66,67] (Figure 2). Neuroprotective potential was demonstrated also for carvacrol [68][69][70], limonene [71][72][73], geraniol [74,75], citronellol [76], carveol [77], 1,8-cineole [78], paeoniflorin [79], α-pinene [80], and linalool [81]. Guzmán-Gutiérrez et al (2012) reported an antidepressant effect of β-pinene and linalool [82], and Deng et al (2015) found that thymol demonstrated this property in a model of chronic mild stress in mice [83].…”
Section: Introductionmentioning
confidence: 99%
“…Also, limonene inhibited acetylcholinesterase with an IC50 close to that of galantamine. 75 Eddin et al 76 found that limonene can protect rats from rotenone-induced dopaminergic neurodegeneration via regulating apoptosis, neuroinflammation, and hippo signaling.…”
Section: Neuroprotective Activitymentioning
confidence: 99%